Perlawanan Pihak Ketiga Terhadap Sita EksekusiSengketa Jual Beli Tanah(Studi Kasus Di Pn Surakarta) - Ardiyanto, Resa; , Nuswardhani, SH.,SU; , Darsono, SH.,M.H (2016)
Land ownership can occur because of the sale and purchase, donation, exchange, and will. Law No. 5 of 1960 on the Basic Regulation of Agrarian (BAL) there is no mention of the word sale and purchase, but is mentioned as diverted. This study uses normative juridical approach. The reasons are the basis for a side third to file opposition to confiscation of execution in Surakarta PN is on the basis of property rights. Consideration of the judge in the decision regarding the failure by a side third filed opposition to confiscation execution in PN Surakarta is the side third has the right to file a lawsuit for control of parcels of land obtaining through a legal act of buying and selling, side third feel aggrieved by the implementation of the seizure of the execution and resistance. Keywords: confiscation execution, sell and purchase of land, dispute